Psychology of advertising - Konoshenko, Lilia (My University, 2012)
Psychology in advertising has long been used as an effective means to sell a product or service. Understanding the underlying concepts that affect human psychology can help a company better sell their product or alternatively can help a consumer understand marketing strategies that get them to buy products. Психологія в рекламі вже давно використовується як ефективний засіб, щоб продати товар або послугу. Розуміння основних концепцій, які впливають людської психології може допомогти компанії краще продавати свою продукцію або альтернативно може допомогти споживачеві зрозуміти маркетингові стратегії, які вони отримують, щоб купити продукти.
Keywords: psychology of advertising; психологія реклами; психология рекламы; advertising; реклама